Tahlil Bahts al Naqd al Adabi al Nisawiy min Hilal Manzur al Falsafi - Muhammad Naufal Annabil (Journal of Arabic Literature (JaLi), 2021)
The aim of this article is to analyze a feminist Arabic literary criticism research from a philosophical perspective, which includes the ontology, epistemology, and axiology of the research. The research subject analyzed was the poem "Sihru Sītā" which was translated by Usman Arrumi from Indonesian poet; Sapardi Djoko Damono. It can be seen that the diction used in poetry seems to corner the image of women in the form of women's oppression over men. As for the philosophical framework in completing the scientific research process, at least it needs to go through various stages, which include identifying problems, formulating problems, compiling a conceptual framework, formulating hypotheses, research methods that include data collection and analysis methods, and finally in the form of conclusions from research. Scientific knowledge, including Arabic literary research, can be said to be correct when a combination of rationalism and empiricism appears. Rationalism provides a coherent and logical framework of thought, whereas empiricism provides a testing framework to ascertain the correctness of that knowledge.